The infernals (2024) ebook - Parrott, Ryan (The Infernals (2024), 2024)
Succession meets the apocalypse in this epic new series about family, power, legacy, and the end of the world. Abe Morgenstern, the son of Satan, has one month to live. Before he dies, he must decide which of his three wayward children—volatile narcissist Nero, conflicted field operative Jackal, or troubled schoolgirl Bee—will inherit his shadowy empire. But with the forces of Heaven, Hell, and everywhere in between bearing down on them, will they survive long enough to take control of the Apocalypse? And is Abe ready to give up being the Antichrist—or does he have something else up his sleeve? Collects THE INFERNALS #1-5